Evaluation Study on Integrated Dairy Development Project - Planning Commission (Planning Commission, 2003)
The Integrated Dairy Development Project (IDDP) was launched in the year 1993-94 in the non-Operation Flood, backward and hilly areas of the country. The Scheme aims at increasing milk supplies in project areas by increasing milk production, facilitating its marketing through integration of activities relating to production, collection, chilling, processing and sale of milk, ensuring remunerative prices to milk producers and increasing their income, employment and nutritional standards. To achieve the aforesaid objectives, the scheme envisages construction of processing and chilling plants; formation of villages level dairy cooperative societies (DCSs) of the cattle owning households; extension of managerial and operational support to them; their affiliation to the District Cooperative Milk Union and the State
Programme Evaluation Organisation Planning Commission Government of India